The impact of government debt on economic growth: An empirical investigation of Namibia - Kaune, Jaungura (School of Economics, 2019)
This paper examines the impact of government debt on economic growth in Namibia with annual data spanning from 1980 to 2016. The paper investigates whether public debt spurs on or promotes economic growth. We employ an Autoregressive Distribution Lag (ARDL) model that serves as an analysis of the short and long run link between public debt and economic growth. In addition, we explore other possible indicators that are likely to affect economic growth such as government expenditure, inflation, gross fixed capital formation and openness. Our findings are consistent with the existing literature that finds a negative correlation between public debt and economic growth. The results of the long run relationship reveal that public debt has an insignificant negative effect on economic growth in Namibia, however, only government expenditure and openness have a negative effect on economic growth. In the short run, gross fixed capital formation and openness promote economic growth, whereas the effect of public debt on economic growth is negative. Following this set-up, we provide policy recommendations that future debt acquired should be for high priority projects and programs that are well reviewed, self-sustainable and can enhance the productive capacity of Namibia. Moreover, the government should take a firm stand on fiscal consolidation and policies that are pro-growth.